PENGARUH BELANJA PEMERINTAH, INVESTASI DAN PDRB TERHADAP KESEMPATAN KERJA DI KALIMANTAN TIMUR (Periode 2003-2015) - Theresia Militina dan Robin Jonathan (DEDIKASI : Jurnal Ilmiah Sosial, Hukum, Budaya, 2018)
The aim of this research is to know the direct and in direct influence of the government expence, investment and PDRB towards the working opportunity here. The analysis model of it using the one namely path analysis. To test the hipothesis using analysis tool channel by SPSS 16.0. The data used in it is secondary data got from statistic board namely the one consists of cases mentioned above. The analysis using double linear that (1). The govermental expense does not influence anymore to them. In the world the govermental expense influence negative result.